MORTALIDADE POR CÂNCER DE MAMA E CONDIÇÕES DE DESENVOLVIMENTO HUMANO NO BRASIL - COSTA, Larissa Di Leo Nogueira (2017)
INTRODUCTION: Breast cancer is an exacerbated and uncontrollable proliferation of abnormal cells, however, it is one of the most studied cancers because it is a heterogeneous group of diseases. It is considered of relative good prognosis if diagnosed and treated early, the average survival after five years of diagnosis is about 80%. Despite the chances of cure, breast cancer is still the type of cancer that kills most women worldwide and trend growth over the years. OBJECTIVE: To analyze the tendency of breast cancer mortality and socioeconomic factors in the capitals of Brazil from 1998 to 2002 and from 2008 to 2012. METHODOLOGY: This is a descriptive study of a time series using the SIM as data on breast câncer mortality and the IDH provided by the Brazilian Geographic Atlas as data on social conditions. RESULTS: With regard to sociodemographic data, the women majority were white in the first and second quinquennial (71.13% and 61.47%), schooling from 4 to 7 years of formal study (26.22% and 26.42 %), The predominant age was women in their 70 years or older (46.21% and 50.29%). Regarding the mortality rate, the prevalence was higher, considering the ten years, were in the capitals of Brasília (3.3), Rio de Janeiro (1.7), followed by Manaus (1.5), São Paulo (1, 4), Campo Grande, Boa Vista and Cuiabá, all with 1.3. And the lowest rates were demonstrated by the city of Palmas (0.3), Florianópolis (0.5), Belo Horizonte, Salvador and São Luís with 0.6. Regarding the IDH, the cities with the highest IDH in 2000 were Florianópolis (0.76), Vitória and Curitiba with 0.75 and São Paulo with 0.73. The cities with the lowest IDH were Maceió (0.58), Rio Branco (0.59), Manaus (1.2) and Porto Velho (0.61), and the highest IDHs in 2010 were in Florianópolis and Vitória 0.84, Brasília (0.82), Curitiba (0.76) and Belo Horizonte (0.57). The lowest IDHs were the cities of Maceió and Rio Branco with 0.72, Macapá, Porto Velho and Manaus with 0.73. Through this analysis we can conclude that there was a general increase in breast cancer in Brazil, with increasing mortality in most of the capitals studied